2015
DOI: 10.1177/0963721415593724
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function Development

Abstract: Executive function developmentCitation for published version: Chevalier, N 2015, 'Executive function development: Making sense of the environment to behave adaptively' Current Directions in Psychological Science, vol. 24, no. 5, General rightsCopyright for the publications made accessible via the Edinburgh Research Explorer is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…In contrast, children in the high working memory group rated the ordered condition as easier than the random condition, although they still did not choose an ordered arrangement in the free condition. Children in this group may therefore be showing an awareness of task difficulty (Efklides et al, 2006), but lack the ability to use appropriate strategies to support performance (Chevalier, 2015(Chevalier, , 2017.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, children in the high working memory group rated the ordered condition as easier than the random condition, although they still did not choose an ordered arrangement in the free condition. Children in this group may therefore be showing an awareness of task difficulty (Efklides et al, 2006), but lack the ability to use appropriate strategies to support performance (Chevalier, 2015(Chevalier, , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the results of our metacognitive questions demonstrated, it would not necessarily be sufficient to ensure that the task environment had been adapted appropriately. Children would also need to be aware of such changes, and of the benefits they might afford (Chevalier, 2015;Schneider, 2008). However, before firm conclusions are drawn relating to the application to classroom contexts, it would be useful to investigate whether this pattern of results replicates in a more naturalistic setting using meaningful objects, and in tasks that are more closely analogous to learning activities typically encountered in the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not strange that some studies could explain our results from the perspective of working memory. Developmental studies have shown adults’ working memory capacity tends to be larger and their executive function is better than children’s (Chevalier, 2015; Tsubomi and Watanabe, 2017). Given that a number of the attention tasks required the use of both working memory and executive function, it would naturally be easier for adults to complete them.…”
Section: Discussionmentioning
confidence: 99%